A BUSINESS LOGIC MODEL DEVELOPMENT FOR SOFTWARE OPERATIONS (Journal of Universal Science Research, 2025)
This article presents a business logic model development for software operation based on an event-driven approach. The proposed model ensures flexible interaction between users, events, and message generation processes, optimizing software performance. The study focuses on the mathematical representation of business logic and its practical application in automating email notifications. The results demonstrate the efficiency of the proposed model in enhancing adaptability and scalability